The many facets of hyperhomocysteinemia: studies from the Framingham cohorts - Selhub, Jacob (The Journal of nutrition, 2006)
Homocysteine is a sulfur amino acid whose metabolism stands at the intersection of 2 pathways: remethylation, which requires folic acid and B-12 coenzymes, and transsulfuration, which requires pyridoxal-5'-phosphate, the B-6 coenzyme. Data from several studies suggest that mild elevations of homocysteine in plasma are a risk factor for occlusive vascular disease. In the Framingham studies we have shown that plasma total homocysteine concentration is inversely related to the intake and plasma levels of folate and vitamin B-6 as well as vitamin B-12 plasma levels. Almost two-thirds of the prevalence of high homocysteine is attributable to low vitamin status or intake. Elevated homocysteine concentrations in plasma are a risk factor for prevalence of extracranial carotid artery stenosis of at least 25% in both men and women. Prospectively elevated plasma homocysteine is associated with increased total and CVD mortality, increased incidence of stroke, increased incidence of dementia and Alzheimer's disease, increased incidence of bone fracture, and higher prevalence of chronic heart failure. This multitude of relationships between elevated plasma total homocysteine and diseases that afflict the elderly point to the existence of a common denominator that may be responsible for these diseases. Whether this denominator is homocysteine itself or whether homocysteine is merely a marker remains to be determined.